Economic evaluation of integrated farming systems - Chiew, E. (Putra Malaysia Univ., 43400 UPM Serdang, Selangor (Malaysia). Faculty of Agriculture. Dept. of Agribusiness and Information Technology) (2013)
Any shift towards an IFS approach and sustainable agriculture presents new challenges to all concerned, farmers, researchers as well as policy makers. We need to recognize that any move towards a more sustainable system, which is characteristically more complex and risky, be it via the IFS or other approaches, is more information and knowledge intensive. For example, a more diverse rotation demands knowledge of a wider range of diseases, insects and input regimes as well as markets. Experiences in farmer adoption of sustainable practices, such as Integrated Pest Management in Cameron Highlands, revealed that sound ecological farming practices are more demanding in terms of information and knowledge, and that they are observation intensive, knowledge intensive, learning intensive and technology intensive. As such, it is vital to understand and identify the factors determining the adoption of such farming practices. The adoption of any new farming system must meet several criteria. Any such system need not only be financially viable, but practical considerations and social acceptance are just as important. Furthermore, experiences of implementing environmental-friendly farming practices have demonstrated that farmers would need economic incentives to support and encourage the transition to an integrated approach. This raises questions about the design of an appropriate support policy and the potential of the market place to provide complementary incentives. Policy support would entail a financial and policy commitment to research and development in IFS.